HAK ASASI MANUSIA DALAM PEMIKIRAN YUSUF QARADHAWI - Faizin, Mu’adil (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
The development of defining fairness gets Human Rights (HAM) idea. But, according to Human Rights, Islamic Law has discriminating dos for religious people. Finally, getting the theory, Islamic Law can’t be accept to  Human Rights. Otherwise, Yusuf Qaradhawi gets the theory that Islam Law has Maqashid Syariah as well as values of Human Rigths. Consequently, the researcher discusses Human Rights Of The Yusuf Qaradhawi Prespective. The research is library research which uses the analysis method to content analysis. The research discovers that Yusuf Qaradhawi divides his idea about Human Rights as three themes; the first, affirming honour of people; the second, affirming Human Rights; the third, struggling weak human rights. The base of his idea is the theorem of the Koran that uses a context approach, further effect of the moderate thinking, and on purpose for solving people condition, nowadays.